High-temperature-resistant glue and copper-clad plate
By combining the modified silicon sol and epoxy resin components, a high-temperature resistant adhesive is formed, which solves the problems of etchant resistance, brittle quality and easy cracking, insufficient flexibility and reduced heat resistance of epoxy resin adhesives, and achieves the problem of The multiple performance improvement of adhesives is suitable for the preparation of high-performance copper clad plates.
Patent Information
- Application Number
- CN202411645313.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-14
AI Technical Summary
The existing epoxy resin adhesives have low etching ability of the etching agent, brittle quality and easy cracking after curing, insufficient flexibility and reduced heat resistance.
Combining modified silica sol and epoxy resin and other components is used to form a high-temperature resistant glue. The glue composition improves the strength and high-temperature resistant properties of the cured film through the cross-linking reaction of the modified silica sol, and passes through long-chain alkane groups. The mass improves hydrophobic ability and corrosion resistance.
It has achieved a significant improvement in adhesive bonding, flexibility, high temperature resistance, acid and alkali resistance and corrosion resistance. It is suitable for flexible substrates such as PEEK and PI, significantly improving the performance of copper clad plates.
Smart Images

Figure CN119432286A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of printed circuit boards, and in particular relates to a high temperature resistant adhesive and a copper clad plate prepared using the high temperature resistant adhesive. Background Art
[0002] This section provides background information related to the present application which does not necessarily constitute prior art.
[0003] Copper clad laminate is a plate-like material made by impregnating the reinforcing material with resin, covering one or both sides with copper foil and hot pressing. It is called copper clad laminate (CCL), or copper clad laminate for short. Copper clad laminate can be divided into paper substrate (FR-1, FR-2, FR-3), epoxy glass fiber cloth substrate (FR-4, FR-5), composite substrate (CEM-1, CEM-3), HDI board (RCC) and special substrate (metal substrate, ceramic substrate, thermoplastic substrate, etc.) according to the reinforcing material. Among them, three-layer flexible copper clad laminate (FCCL, also known as adhesive type flexible copper clad laminate) is widely used in the preparation of circuit boards for lightweight, thin and miniaturized electronic devices because of its low cost, light, thin and flexible characteristics.
[0004] The adhesive used in the existing three-layer flexible copper clad laminate is epoxy resin adhesive. The existing epoxy resin adhesive has the advantages of strong bonding force, high material mechanical strength, strong chemical resistance, good insulation performance, and small curing shrinkage. However, the existing epoxy resin adhesive has the following technical problems:
[0005] 1. Due to the high polarity, high hydrophilicity and high water absorption of epoxy resin adhesive, its corrosion resistance to etchants is low;
[0006] 2. The epoxy resin in the epoxy resin adhesive has the disadvantages of high cross-linking density after curing, brittleness, easy cracking, and insufficient flexibility, which makes it difficult to be used in the field of flexible electronics. The commonly used method to improve the flexibility of epoxy resin is to add toughening agents such as rubber, or to perform softening treatment on the epoxy resin (such as long-chain polyether modification, long-chain fatty acid modification, etc.), but both methods will lead to a decrease in the heat resistance of the epoxy resin adhesive. Summary of the invention
[0007] In view of the technical problems existing in the existing epoxy resin adhesives, the present invention aims to provide an adhesive composition comprising epoxy resin, the cured film of which has excellent adhesion, flexibility, high temperature resistance, acid and alkali stability and corrosion resistance. The adhesive composition provided by the present invention can be applied to flexible substrates such as PEEK and PI. The copper clad laminate prepared by using the high temperature resistant adhesive provided by the present invention has excellent strength, toughness and high temperature resistance, which can greatly improve the performance of the copper clad laminate.
[0008] To achieve the above object, the present invention adopts the following technical solution: a high temperature resistant adhesive, comprising the following components in parts by weight:
[0009] 1-5 parts of modified silica sol, 10-20 parts of epoxy resin, 5-15 parts of nitrile rubber, 10-20 parts of flame retardant, 0.5-3 parts of amine curing agent, 0.02-1 parts of imidazole curing accelerator, 0.2-2 parts of antioxidant, and 30-60 parts of organic solvent.
[0010] Among them, the modified silica sol is a core-shell type silica sol with epoxy groups and long-chain alkane groups. The modified silica sol has excellent compatibility with other components of the high-temperature resistant glue. The modified silica sol participates in the cross-linking reaction to improve the strength and high-temperature resistance of the cured film of the glue composition. The introduction of long-chain alkanes can improve the hydrophobicity of the cured film of the high-temperature resistant glue, reduce the risk of the cured film being corroded by the etching solution, and improve the glue's anti-corrosion ability.
[0011] The modified silica sol is prepared by using orthosilicate compounds, silane coupling agents with epoxy groups, and silane coupling agents with long-chain alkane groups as raw materials, and undergoing a sol-gel reaction process to generate a silica sol having a nano-silica sol as a core and a silane hydrolyzate with epoxy groups and long-chain alkane groups on the surface as a shell. More specifically, the preparation process includes:
[0012] Step 1: Disperse an orthosilicate compound in a solvent, which may be methanol, ethanol, isopropanol, n-butanol or acetone, and then add deionized water as a hydrolyzing agent. Under acidic conditions, the orthosilicate compound reacts with the deionized water to generate a silica sol with hydroxyl groups on the surface.
[0013] Step 2: Under acidic conditions, a silane coupling agent with an epoxy group, a silane coupling agent with a long-chain alkane group and the silica sol with a hydroxyl group generated by the reaction in step 1 are reacted to generate a core-shell silica sol with an epoxy group and a long-chain alkane group through the reaction of the alkoxy group with the hydroxyl group on the surface of the silica sol.
[0014] The orthosilicate compound is ethyl orthosilicate, methyl orthosilicate, isopropyl orthosilicate, butyl orthosilicate or a mixture thereof, preferably ethyl orthosilicate. The silane coupling agent with epoxy group is 3-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560), 3-(2,3-epoxypropoxy)propyltriethoxysilane, 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane or a mixture thereof, preferably 3-(2,3-epoxypropoxy)propyltrimethoxysilane. The silane coupling agent with long-chain alkane group is dodecyltriethoxysilane, dodecyltrimethoxysilane, hexadecyltriethoxysilane, hexadecyltrimethoxysilane, octadecyltriethoxysilane, octadecyltriethylmethylsilane or a mixture thereof, preferably dodecyltrimethoxysilane (12-TMOS).
[0015] Among them, the epoxy resin is the main resin, and the epoxy resin can be various epoxy resins known in the art. From the perspective of improving the heat resistance of the high temperature resistant adhesive, the epoxy resin includes but is not limited to bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, bisphenol AD epoxy resin, phenolic epoxy resin, trifunctional epoxy resin, tetrafunctional epoxy resin, multifunctional phenolic epoxy resin, dicyclopentadiene (DCPD) epoxy resin, phosphorus-containing epoxy resin, paraxylene epoxy resin, naphthalene-type epoxy resin (such as naphthol-type epoxy resin), benzofuran-type epoxy resin, isocyanate-modified epoxy resin or a combination thereof. The novolac epoxy resin may be phenol novolac epoxy resin, bisphenol A novolac epoxy resin, bisphenol F novolac epoxy resin, biphenyl novolac epoxy resin, phenol benzaldehyde epoxy resin, phenol arylalkyl novolac epoxy resin or o-methylphenol novolac epoxy resin; the phosphorus-containing epoxy resin may be DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (epoxy resin, DOPO-HQ epoxy resin or a combination thereof. The aforementioned DOPO epoxy resin may be selected from DOPO-containing phenol novolac epoxy resin. Epoxy resin, one or more of DOPO-containing ortho-methylphenol novolac epoxy resin and DOPO-containing bisphenol A novolac epoxy resin; the aforementioned DOPO-HQ epoxy resin can be selected from one or more of DOPO-HQ phenol novolac epoxy resin, DOPO-HQ ortho-methylphenol novolac epoxy resin and DOPO-HQ bisphenol A novolac epoxy resin, but is not limited thereto. Preferably, the epoxy resin is selected from bisphenol A epoxy resin, dicyclopentadiene epoxy resin or a mixture thereof.
[0016] Among them, nitrile rubber is a toughening agent used to improve the flexibility and high temperature resistance of the cured film of the high temperature resistant rubber.
[0017] Wherein, the flame retardant is aluminum hydroxide, diethyl aluminum hypophosphite or a mixture thereof.
[0018] Among them, the amine curing agent can be exemplified by 4,4'-diaminodiphenyl sulfone (DDS), 3,3-diaminodiphenyl sulfone, diphenylmethanediamine and dicyandiamide. In order to improve the shear strength and heat resistance of the high temperature resistant adhesive, 4,4'-diaminodiphenyl sulfone (DDS) is selected as the amine curing agent.
[0019] Among them, the imidazole curing accelerator can be exemplified by 1-methylimidazole, 2-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole or a mixture thereof. Preferably, the imidazole curing accelerator is 2-ethyl-4-methylimidazole.
[0020] Among them, the antioxidant can be exemplified by pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (1010), tris[2,4-di-tert-butylphenyl]phosphite (168), tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid (1790), N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide) (1098) or a mixture thereof. Preferably, the antioxidant is selected from antioxidant 1010, antioxidant 1098 or a mixture thereof.
[0021] Among them, the organic solvent can be exemplified by hydrocarbon solvents, ester solvents, ether solvents, alcohol solvents, ketone solvents, amide solvents or mixtures thereof, for example, it can include one or more selected from naphtha, dimethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone, DBE, ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, diethylene glycol butyl ether acetate, dimethyl succinate, dimethyl glutarate, dipropylene glycol methyl ether, dipropylene glycol butyl ether, diacetone alcohol, 3-methoxy butyl acetate, 3-methoxy butyl propionate, propylene carbonate, butyl acetate, diethylene glycol diacetate, acetone, butanone, methyl isobutyl ketone, cyclohexanone, isophorone, diacetone alcohol. In some embodiments, the organic solvent is selected from a mixture of acetone and butanone. In some embodiments, the organic solvent is selected from a mixture of N,N'-dimethylformamide and N,N'-dimethylacetamide.
[0022] It should be noted that, without affecting the technical effect of the high temperature resistant adhesive provided by the present invention, the high temperature resistant adhesive provided by the present invention may also contain other additives, including but not limited to cross-linking agents, accelerators, coupling agents, rheological additives, anti-settling agents, defoaming agents, etc.
[0023] On the other hand, the present invention also provides a copper clad laminate, which is prepared by using the above-mentioned high temperature resistant adhesive, and the copper clad laminate is composed of a high temperature resistant resin film and a copper foil bonded by the high temperature resistant adhesive.
[0024] In some embodiments, the copper clad laminate includes a cured film formed by a high temperature resistant adhesive, which can be prepared by printing the high temperature resistant adhesive on a substrate, drying and curing. The cured film can be present on the substrate in the form of a pattern. The curing temperature can be 140-180°C. The substrate can be a flexible substrate, such as a PI film and a PEEK film. The high temperature resistant adhesive of the present invention is particularly suitable for flexible substrates such as PEEK films and PI films due to its improved flexibility.
[0025] In some embodiments, the preparation process of the copper clad laminate includes:
[0026] Step 1: Apply the high temperature resistant adhesive on the substrate and form a cured film on the surface of the substrate after drying;
[0027] Step 2: stack the copper foil and the cured film and then perform heat pressing to obtain a copper clad laminate.
[0028] The cured film formed by the high temperature resistant adhesive provided by the present invention has excellent heat resistance and corrosion resistance, the peeling strength between the cured film and the substrate is high, and the peeling strength between the cured film and the copper foil is high. The copper clad laminate prepared using the high temperature resistant adhesive has excellent stability.
[0029] The following describes the invention in conjunction with specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings further illustrate the present invention, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention.
[0031] Figure 1 This is a flow chart for preparing the modified silica sol in an embodiment of the present invention.
[0032] Figure 2 It is the Fourier transform infrared absorption spectrum of the modified silica sol in the embodiment of the present invention.
[0033] Figure 3 This is a diagram of the surface state of the copper clad laminate after etching, which was prepared using the high temperature resistant adhesive provided in Comparative Example 6.
[0034] Figure 4 This is a diagram of the surface state of the copper clad laminate prepared using the high temperature resistant adhesive provided in Example 3 after etching. DETAILED DESCRIPTION
[0035] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0036] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0037] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0038] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0039] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0040] Herein, the sum of the percentages of all components of the composition equals 100%.
[0041] Herein, unless otherwise specified, "comprising", "including", "containing" and similar terms cover the meanings of "consisting essentially of" and "consisting of", that is, "A comprises a" covers the meanings of "A comprises a and other", "A consists essentially of a" and "A consists of a". Herein, unless otherwise specified, "consisting essentially of" can be understood as "consisting of more than 80%, preferably more than 90%, more preferably more than 95% of...".
[0042] [Modified silica sol]
[0043] In one or more embodiments, the modified silica sol provided by the present invention is a core-shell silica sol with epoxy groups and long-chain alkane groups, and the preparation method thereof comprises the following steps:
[0044] Step 1, dispersing an orthosilicate compound in a solvent to obtain a mixed solution;
[0045] Step 2: under stirring, slowly add an acid catalyst dropwise to the mixed solution, control the pH value of the solution to 2-4, then add deionized water as a hydrolyzing agent, maintain the reaction temperature at 30-60° C. by heating in a water bath, and hydrolyze the orthosilicate compound under the catalysis of the acid catalyst to generate a silica sol stock solution;
[0046] Step 3: under stirring, add the silane coupling agent with epoxy group and the silane coupling agent with long-chain alkane group to the silica sol stock solution for reaction, maintain the reaction temperature at 40-80°C by water bath heating, and control the pH value of the reaction system to 2-4 by adding the acid catalyst during the reaction process, and concentrate after the reaction to obtain a mixture containing modified silica sol, the concentration method is heating concentration under normal pressure or reduced pressure, and the membrane concentration method can also be used, and the mass concentration of the modified silica sol in the mixture after concentration is 15%-50%. In addition to the modified silica sol, the mixture also includes an organic alcohol solvent, which is methanol, ethanol or isopropanol. The mass ratio of epoxy silane coupling agent to silane coupling agent with long-chain alkane group is 0.2-3:1, and the total amount of the two coupling agents added is 0.5-3:1 to the mass ratio of the orthosilicic acid ester in step 1.
[0047] Preferably, the solvent in step 1 is methanol, ethanol or isopropanol, and the mass ratio of the orthosilicate compound to the solvent is 0.05-0.5:1.
[0048] Preferably, in step 2, the acidic catalyst is sulfuric acid, hydrochloric acid, nitric acid, formic acid or acetic acid, and the molar ratio of the added deionized water to the orthosilicate compound is 2-6:1.
[0049] The preparation process of the modified silica sol used in Examples 1-3 of the present invention is as follows: Figure 1 As shown, the specific preparation steps are as follows:
[0050] Step 1: dispersing 50 g of tetraethyl orthosilicate (TEOS) in 200 g of ethanol to obtain a mixed solution;
[0051] Step 2: under stirring, slowly add hydrochloric acid catalyst dropwise to the first mixed solution, control the pH value of the solution to 3, add deionized water as a hydrolyzing agent, maintain the reaction temperature at 40° C. by heating in a water bath, and hydrolyze the orthosilicate compound under the catalysis of the hydrochloric acid catalyst to generate a silica sol stock solution;
[0052] Step three, under stirring, 15g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560) and 20g of dodecyltrimethoxysilane (12-TMOS) are added to the silica sol stock solution for reaction, the reaction temperature is maintained at 60°C by heating in a water bath, and the pH value of the reaction system is controlled to 3 by adding the hydrochloric acid catalyst during the reaction process. After the reaction is completed, the mixture is concentrated under reduced pressure to obtain a mixture containing 30%wt of modified silica sol, and the mixture also contains 70wt% of ethanol solvent.
[0053] The Fourier transform infrared absorption spectra of the modified silica sol used in Examples 1-3 of the present invention are as follows: Figure 2 As shown in the Fourier transform infrared absorption spectrum of the unmodified silica sol, 801 cm -1 and 1104cm -1 There should be an absorption peak at 463cm caused by the symmetric vibration and antisymmetric vibration of Si-O bonds in silica in the silica sol. -1 There should be an absorption peak caused by the bending vibration of Si-O bonds and an absorption peak at 3423cm -1 There should be a broad absorption peak caused by the large amount of OH on the surface of silica in the silica sol. Figure 2 As shown in the Fourier transform infrared absorption spectrum of the modified silica sol, at 3423 cm -1 There is no absorption peak at 1645 cm-1, indicating that KH560 and 12-TMOS react with the hydroxyl groups on the surface of silica in the silica sol. The spectrum shows that the modified silica sol also has absorption peaks at 1645 cm-1 and 12-TMOS at 1645 cm-1. -1 、1349cm -1 There is an absorption peak at 1645cm -1 The absorption peak at 2939 and 1349 cm is caused by the vibration of epoxy groups, which directly indicates that KH560 with epoxy groups is connected to the surface of silica in silica sol; -1 The absorption peak at is caused by the symmetric stretching and bending vibration of CH, which directly indicates that 12-TMOS with long-chain alkane groups reacted on the surface of silica in the silica sol and was attached to the surface of silica.
[0054] [Examples 1-3]
[0055] Examples 1-3 all provide a high temperature resistant adhesive, and the specific composition ratio is shown in Table 1.
[0056] Table 1
[0057]
[0058] [Comparative Examples 1-4]
[0059] Comparative Examples 1-5 all provide a high temperature resistant adhesive, and the specific composition ratios are shown in Table 2.
[0060] The preparation method of the high temperature resistant glue provided in Examples 1-3 and the preparation method of the high temperature resistant glue provided in Comparative Examples 1-5 both include the following steps: controlling the stirring speed of the stainless steel stirring cylinder to 500 rpm, placing the components of the high temperature resistant glue in the stirring cylinder and stirring them evenly, and then grinding them with a sand mill to obtain the final fineness to obtain a high temperature resistant glue with a fineness of ≤10 μm.
[0061] Table 2
[0062]
[0063] [Comparative test]
[0064] The high temperature resistant adhesive provided in Examples 1-3 and the high temperature resistant adhesive provided in Comparative Examples 1-5 were tested as follows:
[0065] (1) Test the viscosity of high temperature resistant glue;
[0066] (2) Testing the heat resistance of the cured film formed by the high temperature resistant adhesive: The glass transition temperature (Tg) of the cured film of the high temperature resistant adhesive is tested by a dynamic mechanical analyzer (DMA) according to the method described in IPC-TM-6502.4.24.4, and the heat resistance of the cured film is evaluated by the glass transition temperature;
[0067] (3) applying the high temperature resistant adhesive to the surface of a polyimide film (PI), drying and curing the PI film to form a 30 μm thick cured film, and testing the peel strength (180° peeling) of the cured film on the PI film;
[0068] (4) The high temperature resistant adhesive was coated on the surface of the polyimide film (PI), and a 30 μm thick cured film was formed on the surface of the PI film after drying and curing. Then, the PI film and the cured film were bent together for 200 times, and the peel strength of the cured film on the PI film after bending was tested.
[0069] The results of the above tests are shown in Table 3.
[0070] The high temperature resistant glue provided in Examples 1-3 and the high temperature resistant glue provided in Comparative Examples 1-5 are used to prepare copper clad laminates, respectively. The specific steps are as follows: the high temperature resistant glue is applied to both end surfaces of a polyimide film (PI), and a 30 μm thick cured film is formed on both end surfaces of the PI film after drying and curing, and an ultra-low surface roughness copper foil with a thickness of 18 μm is respectively covered on the upper and lower end surfaces of the PI film, and the copper clad laminate is obtained by hot pressing in a vacuum press at a pressure of 5 MPa and a temperature of 150°C for 1.5 hours. The copper clad laminate is tested as follows, and the surface state of the copper clad laminate after the test is visually observed to determine whether it is qualified. If the surface of the copper clad laminate after the test does not bubble and does not degumming, it is judged to be qualified (corresponding to the mark "○" in Table 2); if the surface of the copper clad laminate after the test bubbles and / or degumming occurs, it is judged to be unqualified (corresponding to the mark "×" in Table 2).
[0071] (1) Place the copper clad laminate in an environment of 285°C for 12 hours to test its heat resistance stability;
[0072] (2) using existing etching processes and etching solutions to obtain patterned circuits on the surface of the copper clad laminate, and testing the corrosion resistance of the copper clad laminate to the etching solution;
[0073] (3) Place the copper clad laminate at 65°C for 12 hours, then place it in 2% hydrochloric acid mist for 12 hours to test the heat and acid resistance of the copper clad laminate;
[0074] (4) Place the copper-clad laminate at 65°C for 12 hours, then place it in 2% sodium hydroxide alkaline mist for 12 hours to test its heat resistance and alkali resistance stability;
[0075] The results of the above tests are shown in Table 3.
[0076] Table 3
[0077]
[0078] Figure 3 The surface state of the copper clad laminate prepared by using the high temperature resistant adhesive provided in Comparative Example 6 after etching is shown. After etching, part of the copper foil is lifted, that is, the copper foil and the cured film of this part are separated. Figure 4 The surface state of the copper clad laminate prepared using the high temperature resistant adhesive provided in Example 3 after etching is shown. No blistering or debonding occurs on the surface after etching, indicating that the cured film of the high temperature resistant adhesive provided by the present invention has excellent corrosion resistance.
[0079] As can be seen from Table 3, the high temperature resistant adhesive of the present invention has strong bonding strength, excellent heat resistance (glass transition temperature is greater than 160°C), and excellent flexibility, and can be applied to flexible substrates such as PEEK and PI, and can be applied to fields with high heat resistance requirements, such as automobiles, high-speed railways, aerospace, military industry, etc. The copper clad laminate prepared by the high temperature resistant adhesive provided by the present invention has excellent heat resistance, corrosion resistance, heat resistance, and alkali resistance, and the performance stability of the copper clad laminate is remarkable.
[0080] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0081] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A high temperature resistant adhesive, characterized in that: The high temperature resistant adhesive comprises the following components in parts by weight: 1-5 parts of modified silica sol, 10-20 parts of epoxy resin, 5-15 parts of nitrile rubber, 10-20 parts of flame retardant, 0.5-3 parts of amine curing agent, 0.02-1 parts of imidazole curing accelerator, 0.2-2 parts of antioxidant, and 30-60 parts of organic solvent; The preparation process of the modified silica sol comprises: Step 1: Disperse an orthosilicate compound in a solvent, wherein the solvent is methanol, ethanol, isopropanol, n-butanol or acetone, and add deionized water as a hydrolyzing agent. Under acidic conditions, the orthosilicate compound reacts with the deionized water to generate a silica sol having a hydroxyl group on the surface; Step 2: Under acidic conditions, a silane coupling agent with an epoxy group, a silane coupling agent with a long-chain alkane group and the silica sol are reacted to generate the modified silica sol.
2. The high temperature resistant adhesive according to claim 1, characterized in that: The orthosilicate compound is ethyl orthosilicate, methyl orthosilicate, isopropyl orthosilicate, butyl orthosilicate or a mixture thereof; The silane coupling agent with epoxy group is 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propyltriethoxysilane, 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane or a mixture thereof; The silane coupling agent with a long-chain alkane group is dodecyltriethoxysilane, dodecyltrimethoxysilane, hexadecyltriethoxysilane, hexadecyltrimethoxysilane, octadecyltriethoxysilane, octadecyltriethylmethylsilane or a mixture thereof.
3. The high temperature resistant adhesive according to claim 2, characterized in that: The orthosilicate compound is ethyl orthosilicate, the silane coupling agent with epoxy group is 3-(2,3-epoxypropoxy)propyltrimethoxysilane, and the silane coupling agent with long-chain alkane group is dodecyltrimethoxysilane.
4. The high temperature resistant adhesive according to claim 1, characterized in that: The epoxy resin is bisphenol A epoxy resin, dicyclopentadiene epoxy resin or a mixture thereof.
5. The high temperature resistant adhesive according to claim 1, characterized in that: The flame retardant is aluminum hydroxide, diethyl aluminum hypophosphite or a mixture thereof.
6. The high temperature resistant adhesive according to claim 1, characterized in that: The amine curing agent is 4,4'-diaminodiphenyl sulfone.
7. The high temperature resistant adhesive according to claim 1, characterized in that: The imidazole curing accelerator is 2-ethyl-4-methylimidazole.
8. The high temperature resistant adhesive according to claim 1, characterized in that: The antioxidant is selected from antioxidant 1010, antioxidant 1098 or a mixture thereof.
9. The high temperature resistant adhesive according to claim 1, characterized in that: The organic solvent is a hydrocarbon solvent, an ester solvent, an ether solvent, an alcohol solvent, a ketone solvent, an amide solvent or a mixture thereof.
10. A copper clad laminate, characterized in that: The copper clad laminate is composed of a high temperature resistant resin film and a copper foil bonded by the high temperature resistant adhesive described in claims 1 to 9.